Pelatihan Observasi Sampah di SMA Negeri 7 Mataram: Mendorong Inovasi Siswa dalam Pengelolaan Lingkungan - Siti Nurhidayati; Khaeruman Khaeruman (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
Waste observation training at SMA Negeri 7 Mataram aims to improve students' environmental awareness and skills in waste management through a participatory approach. This activity was carried out in three stages: preparation, implementation, and evaluation, which actively involved students in observing and analyzing data related to waste in the school environment. The findings showed that plastic (45%) and organic (35%) waste dominated, reflecting the pattern of single-use plastic consumption. This training succeeded in improving students' analytical skills in recognizing types and priorities of waste management and instilling awareness to sort waste based on its characteristics. The obstacles found such as limited time and student experience indicate the need to develop sustainable programs that include composting and plastic recycling. It also emphasizes the importance of providing more intensive training and long-term support. This training provides a foundation for similar programs in the future to build a culture of environmental care among the younger generation.